Parkinson's disease related signal change in the nigrosomes 1–5 and the substantia nigra using T2* weighted 7T MRI - Schwarz, Stefan Theodor; Mougin, Olivier; Xing, Yue; Blazejewska, Anna; Bajaj, Nin; Auer, Dorothee P.; Gowland, Penny (Elsevier, 2018)
Improved markers for the progression of Parkinson's disease (PD) are required. Previous work has proven that iron dependent MRI scans can detect the largest Nigrosome (N1) within the substantia nigra (SN) pars compacta and changes in PD. Histopathological studies have shown that N1 is particularly affected in early PD whereas the other nigrosomes (N2–N5) and the surrounding iron-rich SN are affected later. In this study we aimed to determine whether MRI can detect the smaller nigrosomes (N2–N5) and whether graded signal alterations can be detected on T2*-weighted MRI at different disease stages consistent with histopathological changes.